Rural women workforce : the changing socio-economic scenario - Singh, Arun Kumar, Dr.; Singh, Shashi (New Delhi : Regal Publications, 2009)
Study conducted in Jaunpur District of Uttar Pradesh, India.
Includes index.
Includes bibliographical references (p. [243]-248).
Keywords: Rural women -- India -- Jaunpur (District) -- Economic conditions; Rural women -- India -- Jaunpur (District) -- Social conditions; Women employees -- India -- Jaunpur (District).; Women in development -- Government policy -- India -- Jaunpur (District)